EFEKTIVITAS BEBERAPA VAKSIN NEWCASTLE DISEASE (ND) PADA AYAM LAYER TERHADAP TITER ANTIBODY JUMLAH LEUKOSIT DAN ERITROSIT - Deni Febriasyah Hasbawi ,; Kurniawan Sinaga , (Jurnal Cakrawala Ilmiah, 2025)
This study aims to determine the effectiveness of several newcastle disease vaccines in layer chickens on antibody titers, leukocyte counts, and erythrocytes with the hope that administering newcastle disease vaccines to layer chickens will have a positive effect on antibody titers, leukocyte counts, and erythrocytes so that this study can help the public understand newcastle disease vaccination in layer chickens with various vaccines and their effectiveness. This study shows the results of a total of 20 blood samples of laying hens obtained a picture of the blood titer results from the four treatments showed a picture of antibody titers that were still protective, namely ≥4 HI Log2 with the highest value of 11.78 HI Log2, with leukocyte values that increased with the highest value of 32.81 103/µL so that it is able to provide better immune protection against the new castle disease virus, while the number of erythrocyte cells increased although it was still within the normal range so that it did not have a significant effect on increasing the immunity of laying hens, so in a simple sense vaccination with the newcastle disease vaccine is able to provide immune protection for laying hens with an increase in the number of leukocyte cells and does not affect the number of erythrocyte cells so that it is still within the normal range.